惡性腫瘍に於ける免疫学的現象の研究 - 長沢 文龍 (Gann, 1951)
1. Of immunological phenomena of malignant tumors, I have obseved, by satisfactorily exact experimental methods, the following six cases: immunity in re-transplantation, effects of tumor vaccine, passive immunity, agglutination, precipitation, and cutaneous reaction; and found it clear that antibodies to tumor cells are produced by transplanting tumor cells. Production of antibodies was increased to some degree along with the propagation of tumors, but the productivity was not so strong as seen in the bacteriological field. The most distinctive fact I noticed was the agglutination of tumor cells.Eaton (15), who tested agglutination of Plasmodium knowlesi by immune serum from chronically infected and superinfected monkeys, reported that the titers of agglutination were given at dilutions of only 1:16 to 1:64± in the acute stages and at dilutions of 1:256 to 1:1, 024± in the chronic stages or after some ten infections of this disease were received.Agglutinin that operates upon tumor cells is also found, in a small amount (about 1:25), even in normal animals. This gradually increases (1:200) with tumor cells implanted, but not so by the sensitization with other cells, for instance, liver cells or red cells. Therefore I may safely say that this phenmenon is specially confined to tumor cells.Tumor vaccine forms a subject of interesting study. Successive inoculations of this vaccine were carried out in diverse ways before and after the transplantation of tumors, but the growth of tumors could not be restrained.In regard to the effects of serum of cured animals, Takeda (16) and his cooperators reported that they transplanted Yoshida Sarcoma in successive generations of white rats of Wister-strain and with 0.5cc of serum from these spontaneously cured animals they were successful in completely preventing tumors from proliferation.In my experiments serum from cured animals proved effective to some degree in retarding the proliferation of implanted tumors, but not so powerfully as to hinder it.2. I investigated a cutaneous reaction which was considered as neutralizing phenomenon of tumor toxin.Recently considerable attention has been paid to such reactions (17) as diagnostic methods of cancer and these methods have a much higher positivity as compared with other means of diagnosis. My method of reaction can be said to be a new one as to obtaining an antigen. Certainly this reaction was produced sooner than several other diagnostic methods I tried, but could not be expected in the early period after transplantation. In other words, even such a reaction requires a certain time in letting the body respond to it. Here lies difficulty of diagnosis of cancer. On the other hand, however, there is a fact that blood sugar increases in amounts describing a certain curve in the early stage after transplantation. With this fact into consideration the decision of positivity may be hastened by judging from cutaneous reaction and blood sugar titer together. That is, in the early period in case the blood sugar titer is high, the cutaneous reaction may safely be judged as certain positive, even though it may by itself be apparently uncertain positive. 惡性腫瘍における免疫学的現象の観察に最も適当な吉田肉腫を用いて,次の諸項目に就て実驗を行つた。1.再移植免疫の実驗;第1回の移植により,第2回の移植はその成長を或程度遅延させるが,完全に抑制される事実は認めることは出來ない。2.腫瘍細胞ワクチンの効果に関する実驗;移植された腫瘍の発育に対して抑制的には作用を示さない。3.被動性免疫の実驗;自然治癒した動物の血清を用いて,体外で腫瘍細胞に混じても,又は移植後に注入しても腫瘍の発育を著しく阻害することは出來ない。4.腫瘍細胞の凝集反應;腫瘍動物の血清中には腫瘍細胞に対する凝集素が明に増加することを認める。この現象は今回の実驗中最も顯著な事実に属する。5.腫瘍細胞抽出液による沈降反應;腫瘍細胞の蒸溜水エキスを腫瘍動物の血清に加えると微弱ながら反應陽性を認める。6.皮内反應;腫瘍細胞のアルコールエキスを用いて腫瘍動物に1種の皮内反應を発現させることが出來る。反應は移植後6日目以後において最も著明である。以上の実驗成績から,腫瘍細胞を移植することにより,腫瘍細胞に対する抗体が作られることは明である。そして,抗体は腫瘍の増殖と共に或程度増加することも認められる。併し,その強さは細菌学領域における樣に著しいものでは無いと言わねばならない。尚ほ,吉田肉踵動物では移植後血糖價が一定の曲線を以て推移し,4日目にはその頂点を示す。この時期には皮内反應は不確実陽性であるが,血糖價と合せて判定すれば,この反應を確実陽性と認めることが出來る。人癌でも,早期においては概して血糖價の上昇を示す場合が多いと報告されておるから,人体の場合にも皮内反應と同時に血糖價を考慮に入れれば,この反應の判定をより早期に,且つ確実にするだろうと考える。